Educating for autonomy: Literature as a developer of critical thinking - Andrade, Paulo (2023)
Paulo Freire understands reading as an act of transgression and practice of autonomy for the construction of critical thinking, which is developed by the dialogic relation between reading the world and reading the written word. This paper defends the role of Literature as a space capable of mobilizing a complete field of knowledge and an effective instrument of social innovation, insofar as it contributes to the practice of alterity and diversity. How should the poetic word, formed by a specific language system which takes into consideration the reader’s experience, be presented in the classroom?